Increasing visibility for LGBTQ students: What schools can do to create inclusive classroom communities - Derry L. Stufft (Arizona State University, 2011)
The number of lesbian, gay, bisexual, transgender and questioning students is increasing in schools. School districts, administrators and teachers need to increase awareness of these students and work to make them feel included and welcomed in a safe school environment, one free from offensive languages and practices. This article discusses some of the problems that these students and teachers face and some strategies that educators can use to help them be a valuable part of a learning community.